Volume of the crocodilian brain and endocast during ontogeny - Jirak, Daniel; Janacek, Jiri (PloS one, 2017)
Understanding complex situations and planning difficult actions require a brain of appropriate size. Animal encephalisation provides an indirect information about these abilities. The brain is entirely composed of soft tissue and, as such, rarely fossilises. As a consequence, the brain proportions and morphology of some extinct vertebrates are usually only inferred from their neurocranial endocasts. However, because the morphological configuration of the brain is not fully reflected in the endocast, knowledge of the brain/endocast relationship is essential (especially the ratio of brain volume to endocast volume or the equivalent proportion of interstitial tissue) for studying the endocasts of extinct animals. Here we assess the encephalic volume and structure of modern crocodilians. The results we obtained using ex vivo magnetic resonance imaging reveal how the endoneurocranial cavity and brain compartments of crocodilians change configuration during ontogeny. We conclude that the endocasts of adult crocodilians are elongated and expanded while their brains are more linearly organised. The highest proportion of brain tissue to endocast volume is in the prosencephalon at over 50% in all but the largest animals, whereas the proportion in other brain segments is under 50% in all but the smallest animals and embryos. Our results may enrich the field of palaeontological study by offering more precise phylogenetic interpretations of the neuroanatomic characteristics of extinct vertebrates at various ontogenetic stages.
Keywords: magnetická rezonanční tomografie; aligátoři a krokodýli; Animals; Fossils; Phylogeny; zkameněliny; mozek; lebka; Biological Evolution; fylogeneze; Magnetic Resonance Imaging; Alligators and Crocodiles; biologická evoluce; Brain; Skull; zvířata